Role of ppGpp in rpoS Stationary-Phase Regulation in Escherichia coli - Hirsch, Matthew (American Society for Microbiology, 2002)
The bacterial sigma factor RpoS is strongly induced under a variety of stress conditions and during growth into stationary phase. Here, we used rpoS-lac fusions in Escherichia coli to investigate control acting at the level of RpoS synthesis, which is especially evident when cells approach stationary phase in rich medium. Previous work has shown that the small molecule ppGpp is required for normal levels of RpoS in stationary phase. Despite the attraction of a model in which the ppGpp level controls stationary-phase induction of RpoS, careful measurement of rpoS-lac expression in a mutant lacking ppGpp showed similar effects during both exponential growth and stationary phase; the main effect of ppGpp was on basal expression. In addition, a modest regulatory defect was associated with the mutant lacking ppGpp, delaying the time at which full expression was achieved by 2 to 3 h. Deletion analysis showed that the defect in basal expression was distributed over several sequence elements, while the regulatory defect mapped to the region upstream of the rpoS ribosome-binding site (RBS) that contains a cis-acting antisense element. A number of other genes that have been suggested as regulators of rpoS were tested, including dksA, dsrA, barA, ppkx, and hfq. With the exception of the dksA mutant, which had a modest defect in Luria-Bertani medium, none of these mutants was defective for rpoS stationary-phase induction. Even a short rpoS segment starting at 24 nucleotides upstream of the AUG initiation codon was sufficient to confer substantial stationary-phase regulation, which was mainly posttranscriptional. The effect of RBS-proximal sequence was independent of all known trans-acting factors, including ppGpp.